Pengoperasian Aplikasi RKAS Dalam Pengelolaan Dana Bantuan Operasional Sekolah (BOS) - Shevia Dwi Diantari; Malista Sint Oida Bani; Sonata Al Fatiqh; Syunu Trihantoyo (Lembaga Pengembangan Kinerja Dosen, 2024)
The RKAS application is an information and communication system to facilitate the budgeting, implementation and administration as well as accountability of the School Operational Assistance Fund in primary and secondary education units nationally. This study aims to determine how the RKAS application operates in assisting the management of the School Operational Assistance Fund (BOS). The method used in this research is a systematic literature review with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) model. The data for this study was taken from the google scholar database. The results of this study show that the RKAS application is very helpful in managing BOS funds, besides that the RKAS application can also ensure accountability, transparency, effectiveness, and efficiency in its management. ARKAS allows schools to plan, implement, and report the use of funds efficiently. The use of ARKAS also makes it easier to monitor and evaluate the use of BOS funds. The use of the RKAS application has a significant impact on school financial management, the operation of a good RKAS application will have a good impact on schools, and vice versa. Thus, schools are obliged to use the RKAS application as a guide in managing BOS funds, so that BOS funds can be managed accountably and transparently and help in school management.